2022
DOI: 10.3389/fphar.2022.841410
|View full text |Cite|
|
Sign up to set email alerts
|

Propofol Protects Myocardium From Ischemia/Reperfusion Injury by Inhibiting Ferroptosis Through the AKT/p53 Signaling Pathway

Abstract: The molecular mechanism underlying the protective role of propofol against myocardial ischemia/reperfusion (I/R) injury remains poorly understood. Previous studies have shown that ferroptosis is an imperative pathological process in myocardial I/R injury. We hypothesized that propofol prevents myocardial I/R injury by inhibiting ferroptosis via the AKT/p53 signaling pathway. The ferroptosis-inducing agent erastin (E) and AKT inhibitor MK2206 (MK) were used to investigate the role of propofol in myocardial I/R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Apart from these drugs/compounds, a variety of agents with different biological activities have been shown to inhibit ferroptosis in MIRI. Propofol, a frequently used anesthetic agent, has been shown to protect against myocardial injury by suppressing I/R-induced ferroptosis through the AKT/p53 signaling pathway [ 72 ]. Ferulic acid (FA), the main active component of Angelica sinensis , was reported to alleviate MIRI by enhancing AMPKα2 expression-mediated ferroptosis inhibition [ 73 ].…”
Section: Therapeutic Strategies Targeting Ferroptosis In I/r Injurymentioning
confidence: 99%
“…Apart from these drugs/compounds, a variety of agents with different biological activities have been shown to inhibit ferroptosis in MIRI. Propofol, a frequently used anesthetic agent, has been shown to protect against myocardial injury by suppressing I/R-induced ferroptosis through the AKT/p53 signaling pathway [ 72 ]. Ferulic acid (FA), the main active component of Angelica sinensis , was reported to alleviate MIRI by enhancing AMPKα2 expression-mediated ferroptosis inhibition [ 73 ].…”
Section: Therapeutic Strategies Targeting Ferroptosis In I/r Injurymentioning
confidence: 99%
“…Ferroptosis is a new-found form of cell death characterized by iron-dependent overwhelming lipid peroxidation [ 32 ]. It has been shown that ferroptosis is involved in various pathological conditions [ 33 , 34 ]. We also previously found that apoptosis is increased in the penis of diabetic rats, but the use of apoptosis inhibitors can only partially reduce cell death, and the improvement of penile erectile function was also not obvious, suggesting that apoptosis is not the predominant form of cell death in corpus cavernosum [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, propofol inhibited ferroptosis via the AKT/P53 signaling pathway, thereby protecting CM from I/R injury. Specifically, it reduced SOD and iron accumulation, decreased lipid peroxidation levels, thereby increasing the expression of antioxidant enzymes [ 68 ]. Ferroptosis as one of the mechanisms of CM death after myocardial I/R has been widely demonstrated, and inhibiting ferroptosis may be an effective way to attenuate myocardial I/R injury.…”
Section: Ferroptosis Involvement In the Pathological Progression Of Chdmentioning
confidence: 99%
“…Therefore, antioxidants may be the most promising ferroptosis inhibitors for widespread use. Excavating drugs with inhibiting ferroptosis from clinically available drugs may provide new options for treating CHD more quickly, such as vitamin E, fluvastatin, puerarin, dexmedetomidine, and propofol [ 41 , 60 , 65 , 67 , 68 ].…”
Section: Ferroptosis As a Novel Therapeutic Target For Chdmentioning
confidence: 99%